Reasons and types of domestic violence against married women: a community based cross sectional study in urban slums of Pune, India - Neetu Choudhary; Murarkar, Sujata Kapil; Deshmukh, Rupeshkumar (International Journal Of Community Medicine And Public Health, 2024)
Background: Worldwide, domestic violence against females is common across religion, culture, socio economic class and ethnicity. Objective was to assess reasons and types of domestic violence against married women in urban slums of Pune. Methods: A community based cross sectional study was undertaken amongst 405 married women above 18 years of age. Chi square test was used to find an association between the different demographic variables with respect to domestic violence. Univariate logistic regression was used to find the Odds ratio between the domestic violence and different risk factors. Results: Prevalence of domestic violence was 37.28%. Commonest reasons reported for domestic violence was ‘not doing household work properly’ (23.47%). Duration of marriage (p<0.05), total number of children (p<0.05), type of family (p<0.05) and alcohol consumption by husband were significantly associated with domestic violence. Conclusions: Present study revealed that duration of marriage, total number of children, type of family and alcohol consumption by husband are the factors significantly associated with domestic violence against married women. Sessions on de -addiction and preventing the family from domestic violence arising due to it can be taken.